Tourist satisfaction at nature-based tourism destination around Kota Kinabalu, Sabah - Hamimah Talib (Universiti Malaysia Sabah, 2020)
Kota Kinabalu, Sabah has been famed as Nature Resort City where nature-based destinations in and around the city have been the major tourist attractions. Nonetheless, the question whether the visitors are satisfied with their experience at the major nature-based tourism destination or otherwise is still vague. The purpose of this study is to understand the recreational experience and satisfaction of tourist in selected nature-based tourism sites in Kota Kinabalu, Sabah. A mixed method approach incorporating quantitative data derived using Driver’s Recreation Experience Preference Scale, and qualitative data using Herzberg’s Critical Incident Technique were deployed. The sampling technique used in this study was purposive non-probability sampling with the participation of 240 tourists. Factor analysis was run on the quantitative dataset to derive the major outcome which is the set of profile on tourist recreational experience. While content analysis was conducted on the qualitative dataset to derive explanation for tourist satisfaction/dissatisfaction. Triangulation between the two types of datasets strengthens the major finding which is the tourist satisfaction in nature-based tourism destination around Kota Kinabalu, Sabah. The finding of this study is crucial for satisfaction enhancement and critical for identification of areas to be improved, subsequently solutions to be recommended.